The Way of Yield Increasing and Cost Reducing in Agriculture: Smart Irrigation and Fertigation - Muhammed Karaşahin; Özgür Dündar; Ahmet Samancı (Turkish Journal of Agriculture: Food Science and Technology, 2018)
The plants can only use the around 50% of the applied nitrogenous fertilizer. It has been observed that the dynamic fertigation applications help to improve the fertilizer effectiveness. In the dynamic fertigation approach, water and plant nutritional elements are calculated and determined according to the plant dry matter generation rate and root volume. Smart agriculture is an knowledge based decision making approach established upon quantification and observations of the changes in each level of production. With this system, saving can be provided by only supplying the plant’s daily need of water and fertilizer and preventing the excess irrigation and fertilizing, so yield increase can be achieved by keeping away the plants from the stress conditions. Agricultural production can be increased five times by irrigation but shortening in water sources and decrease in quality reasoned by fast growing are restricted of irrigation which is the main user of freshwater sources. Increasing the water and fertilizer effectiveness with the smart irrigation techniques which can save water and fertilization management applications are the essential strategies to be able to reach the yield increase in order to supply the growing food needs of developing population and help to minimize the environmental damage. In the study, the researches and applications related to smart irrigation and fertilization were tried to be included in a wide scope and tried to keep a light to obtain higher yield with less water and fertilizer use in agriculture.